Long Term Mnemonic: Keefektifan Teknik Keyword Mnemonic untuk Meningkatkan Memori Jangka Panjang Kosakata Bahasa Inggris - Alibasya, Azzahra Asihputri; Aditya, Shakuntala Fatira; Putri, Laras Febriana; Dwi Farisandy, Ellyana (Journal of Research and Measurement in Psychology: JPPP, 2024)
The Psychology Major at X University uses a lot of English references. Learning effectiveness is reduced for students with poor understanding of English. Understanding a language is related to long-term memory, the system responsible for storing various information for a long time. Mnemonic techniques can be used to organizing memory. This study aims to determine whether the mnemonic method can help students to improve long term memory in mastering English vocabulary. Participants are active students of the Psychology Major at X University, aged 18-22 years. The division of participants into the experimental and control group was carried out by random assignment. The instrument used a module containing 35 English vocabularies, the mnemonic was given to the experimental group module. Posttest in this study used 20 multiple choice questions. Each correct answer is given a score of 5 and wrong is 0. This study shows that there is no significant difference (t = 0.97, Sig. = 0.17) between the experimental group (mean = 69.18, SD = 7.07) with the control group (mean = 59.23, SD = 7.36). So, it can be concluded that the mnemonic technique does not make a significant difference in learning English vocabulary